A GIS-based approach to analyzing warning siren networks: An analysis of Riley and Wabaunsee Counties, Kansas - Stimers, Mitchel James (Applied Geography Conferences, 2006)
Tornadoes are deadly storms that can cause a great deal of destruction in the communities they strike. Although warning systems have been improved upon in recent years, tornadoes still pose a serious threat to property, and more seriously, human life. The location of emergency warning sirens is an important factor in reducing vulnerability and providing people the necessary leadtime to take shelter when a tornado is approaching. This paper will examine some of the geographical and population-driven considerations through an analysis of the siren networks of two counties, Riley and Wabaunsee, in northeastern Kansas.
Keywords: Tornado warning siren network; Warning siren coverage; GIS